Professor Walery Czekman (Valerijus Čekmonas) in the Light of His over 25 Years of Correspondence - Smułkowa, Elżbieta (Slavistica Vilnensis, 2025)
Professor Elzbieta Smulkova's memories of the Vilnius University professor Valerijus Chekmonas are based on materials from personal correspondence that continued over many years. Cooperation in the field of Polish and Belarusian studies was very fruitful, although in their course scientists were more than once faced with the need to solve complex issues.
Keywords: Vilnius university; history of Slavic studies; polonistic studies; Valerijus Chekmonas